2022
DOI: 10.3390/nu14153200
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Sodium Availability and Food Sources from 2018 to 2019 and Its Trends during the 2004–2019 Period in Costa Rica

Abstract: Sodium availability and food sources in 2018–2019 were estimated and trends analyzed for 15 years (2004–2019) in Costa Rica. Food purchase records from the National Household Income and Expenditure Survey (ENIGH) 2018–2019 were converted to energy and sodium using food composition tables measuring “apparent consumption”. Foods were classified by sodium content. ENIGH is a probabilistic, stratified, two-stage and replicated national survey, carried out regularly by the national statistics institution. Results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…However, this suggests that the current local limits are too lax compare with the regional targets and require further adjustment; and the necessity to include sodium source food groups that are currently not included, such as cheese and puff pastries 20 . While Costa Rica has a voluntary sodium reduction strategy to reduce sodium levels in some key food categories , progress has been monitored continuously [21][22][23] . A study published by Vega-Solano et al in 2019 showed 87% compliance with the voluntary national sodium targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this suggests that the current local limits are too lax compare with the regional targets and require further adjustment; and the necessity to include sodium source food groups that are currently not included, such as cheese and puff pastries 20 . While Costa Rica has a voluntary sodium reduction strategy to reduce sodium levels in some key food categories , progress has been monitored continuously [21][22][23] . A study published by Vega-Solano et al in 2019 showed 87% compliance with the voluntary national sodium targets.…”
Section: Discussionmentioning
confidence: 99%
“…While Costa Rica has a voluntary sodium reduction strategy to reduce sodium levels in some key food categories, progress has been monitored continuously 2123 . A study published by Vega-Solano et al in 2019 showed 87% compliance with the voluntary national sodium targets.…”
Section: Discussionmentioning
confidence: 99%
“…In the country, the most recent studies indicate that sodium intake (4.42 grams/person/day (g/p/d)) was more than double the maximum recommendation established by the Organization World Health Organization (WHO) (2000mg of sodium equivalent to 5 g of salt/p/d) [6,7]. Recent modeling studies estimated that a 15 to 46% decrease in daily salt intake could prevent 5 to 13% of deaths due to CVD [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is why international organizations such as the World Health Organization (WHO) address out-of-home eating as an environmental determinant of health [11] [12] [13]. In Costa Rica, the main sources of sodium are "processed culinary ingredients" (salt and condiments) and "ultra-processed foods and beverages" [6] [7] [8].…”
Section: Introductionmentioning
confidence: 99%